Factors Influencing Behavioural Intention of Farmers to Use E-Learning Module on Climate-Smart Horticulture in Arunachal Pradesh (Indian Journal of Extension Education, 2021)
The study developed a theoretical model based on the technology acceptance model (TAM) called the e-learning acceptance model (ELAM) during 2020. Using structural equation modelling (SEM), farmers’ behavioural intention to use (BIU), an e-learning module on Climate-Smart Horticulture was investigated. The facilitating condition, followed by perceived ease of use, attitude toward e-learning, and self-efficacy, was found to be the most influential predictor of behavioural intention to use an e-learning module by the structural equation model (SEM). The endogenous variable BIU having R2 value of 0.62 indicated that the exogenous variables viz., FC (Facilitating Condition), PEU (Perceived Ease of Use), ATT (Attitude toward e-learning) and SE (Self-Efficacy) had jointly explained and predicted 62 per cent of accuracy on BIU in ELAM.